APPLICATION OF AUGMENTED REALITY AS A LEARNING MEDIA OF MOLLUSCA GROUP ANIMAL RECOGNITION AND ITS HABITAT BASED ON ANDROID - Olvi Lorensky Yeztiani; Qadhli Jafar Adrian; Ahmad Ari Aldino (Universitas Teknokrat Indonesia, 2022)
Augmented Reality is a technology that is currently developing, this technology can combine the virtual world with the real world. Augmented Reality technology has been developed in many fields. One application of Augmented Reality technology is in the field of education, as a learning medium. Currently, there are still many learning media that use books and blackboards as a means of delivering material so that students feel bored to learn because the material obtained is only in the form of text and two-dimensional images. Submission of material like this is considered less informative and interactive for students so that it has an impact on decreasing student interest in learning. This Mollusca animal application was created to provide an alternative to easy teaching for biology teachers at SMA N 1 Penawar Aji in providing Mollusca animal material to students of class X majoring in Science, by describing an object in three-dimensional form. With this, students will also understand and be more interested in studying Molluscs. And can make it easier for students to learn how the shape of Mollusca animals and their habitats. This application is made using Unity 3D software. The system development method used in making this application uses the MDLC (Multimedia Development Life Cycle) method. The way this application works is that the camera on the android device functions as an input device that will capture the marker, after the marker is detected the three-dimensional object that has been created will be displayed on the screen. The results of the development of this application can provide convenience for teachers in conveying material about Mollusca animals and students can clearly see the shape of Mollusca animals and their habitats